PENGARUH KEBIJAKAN LUAR NEGERI TERHADAP HUKUM PIDANA INTERNASIONAL: THE INFLUENCE OF FOREIGN POLICY ON INTERNATIONAL CRIMINAL LAW - Ferdiansyah, Ferdy; Pribadi, Riky (Fakultas Hukum Universitas Trisakti, 2023)
The application of international criminal law in Africa is greatly influenced by the foreign policies of international actors and African countries themselves. The foreign policies of international actors, such as Western countries and multilateral organizations, often determine support for or rejection of institutions such as the International Criminal Court (ICC). This international support, whether diplomatic pressure or financial assistance, strengthens the role of international legal institutions in the prosecution of serious crimes in Africa. However, this relationship also gives rise to political tensions, where several African countries see this intervention as a form of neo-colonialism and ignore their national sovereignty. On the other hand, the foreign policies of African countries show complex dynamics. Some countries, such as Botswana, fully support the ICC as a means of ensuring accountability, while others, such as Sudan and Kenya, reject international intervention, especially in cases involving their political leaders. The relationship between African states and the international community in the process of implementing international criminal law reflects the efforts made to balance the need for international justice with the protection of state sovereignty. In this context, the development of regional alternatives such as the African Criminal Court is also a response to tensions with the Western-dominated international legal system.